The efficiency of commercial banks in Indonesia - Chowdhury, Mohammad Abdul Matin; Haron, Razali; Sulistyowati, M.I. Kom; Al Masud, Md. Abdullah (Inderscience, 2021)
Banking sector plays a very important role in economic development through stimulation of savings and investment. The main purpose of this study is to evaluate and compare the banking efficiency between public, private, and commercial banks in Indonesia. The data were collected from consolidated annual reports of 21 commercial banks for the period of 2013–2018. The DEA approach was applied to identify the efficiency of all types of banks and finally compared using the technical efficiency (TE), the pure technical efficiency (PTE) and the scale efficiency (SE). The findings showed that all commercial banks are required to improve their management practices while Islamic banks are comparably better in overall technical efficiency. Finally, these findings suggest banks to improve their efficiency through utilising maximum inputs to produce higher outputs. Policy makers may consider the findings to improve monitoring and regulating the most effective and adequate policies to improve banking growth.